The Influence of Work Environment on Employee Performance at CIMB Niaga Bank - Nadia Putri Iskandar; Tutiek Yoganingsih; Cahyadi Husadha (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the Influence of the Work Environment on Employee Performance at Bank CIMB Niaga where the existence of a supportive work environment will improve employee performance. This study uses a quantitative method with sampling, namely Purposive Sampling. The number of samples used in this study was 33 respondents from PT CIMB Niaga employees. The testing of the research hypothesis was carried out with the help of the SPSS version 25 program. The results of the research that have been carried out are variables that affect each other, namely the work environment has a positive and significant influence on the performance of PT CIMB Niaga employees